Reactivation rates in patients using biological agents, with resolved HBV infection or isolated anti-HBc IgG positivity - Haykır Solay, Aslı; Acar, Ali; Eser, Fatma; Kuşcu, Ferit; Tütüncü, Emin Ediz; Kul, Gülnur; Şentürk, Gönül Çiçek; Gürbüz, Yunus (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Tumor necrosis factor-α (TNF-α) inhibitors and ustekunimab are widely used in autoimmune diseases. It is known that these biological agents cause the reactivation of hepatitis B virus (HBV). There is no standardized strategy to prevent the reactivation in patients with evidence of a previous HBV infection. In our study, anti-HBc IgG-positive patients who received a biological agent were evaluated in terms of HBV reactivation. Materials and Methods: Patients who were followed up for the use of biological agents in our clinic were evaluated retrospectively. Patients with isolated anti-HBc IgG positivity were included in the study. The HBV reactivation data were recorded from the patients’ files retrospectively. Results: Two hundred and seventy-eight patients who received biological treatment were evaluated. Twenty-nine patients with isolated anti-HBc IgG positivity or resolved HBV infection were included in the study. The HBV reactivation was seen in 5 patients (17.2%). Of these patients, 3 were using adalimumab, 1 infliximab, and 1 ustekunimab. It was controlled by antiviral therapy that was started in the early period. Conclusion: Drugs that block TNF-α and ustekunimab cause an increase in viral replication. In literature, the HBV reactivation rate was approximately 1% in HBsAg-negative, anti-HBC IgG-positive cases, whereas it was found to be as high as 17.2% in our study. Patients receiving the immunomodulator therapy should be evaluated for HBV serology before treatment and carefully monitored for HBV reactivation during and after treatment. Cite this article as: Solay AH, Acar A, Eser F, et al. Reactivation rates in patients using biological agents, with resolved HBV infection or isolated anti-HBc IgG positivity. Turk J Gastroenterol 2018; 29: 561-5.